Tenure In Peninsular Malaysia And The Philippines Compared - S. Salasal, Siti Maryam Malinumbay (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1999)
Peninsular Malaysia and the Philippines has its own history of colonial intervention. Each country has a defined system of government and a form of land tenure and administration. However, with the colonial powers' arrival and the introduction of new laws into Peninsular Malaysia and the Philippine archipelago respectively has changed the law which both countries were accustomed to. Thus, giving birth to the new system and eventually culminated the adoption of the National Land Code, 1965 and the Philippines National Land Laws. The Torrens system is the core of the system where the precept epitomized the principle that 'register is the key to title.' Corollary to the above, the Customary tenure (which were the concoction of Islamic law and adat) and land administration was replaced by the system which is western in nature. Hence, in Malaysia, the present land laws and tenure was the by-product of the British land laws and the Philippines were that of the Spanish and eventually the American land laws and tenure.